2019
DOI: 10.26719/emhj.18.019
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk screening of hospitalized children aged < 3 years

Abstract: Background: Identification of children at risk of malnutrition is not easily achieved in hospital settings. Aims: To assess the merits of using the Screening Tool for Risk on Nutritional status and Growth (STRONG kids ) as a nutrition screening tool in hospitalized children aged < 3 years and correlate it with the severity of their nutritional derangements. Methods: This cross-sectional study was conducted on 500 children aged < 3 years admitted to the Children's Hospital, Ain Shams University, Cairo, Egypt. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Fever, burns, ascites or fluid loss can alter the balance between calorie consumption and requirement, which contributes to HAM (Mehta et al, 2013;Shaaban, Nassar & El-Gendy, 2018). In our study, half of the patients with HAM had some kind of gastrointestinal loss although this finding was not statistically significant.…”
Section: Discussioncontrasting
confidence: 67%
“…Fever, burns, ascites or fluid loss can alter the balance between calorie consumption and requirement, which contributes to HAM (Mehta et al, 2013;Shaaban, Nassar & El-Gendy, 2018). In our study, half of the patients with HAM had some kind of gastrointestinal loss although this finding was not statistically significant.…”
Section: Discussioncontrasting
confidence: 67%
“…Another cross-sectional study performed in 500 hospitalized children aged below 3 years in a children's hospital in Egypt found that 37.8% of patients were high risk according to STRONGkids, 62.4% were underweight, 58.4% were stunted, and 57.8% were wasted according to WHO criteria [36]. The STRONGkids score was found to be higher among those who deteriorated in nutritional status, which, together with its significant positive correlation with the duration of hospital stay, emphasized that STRONGkids score could be a predictive tool.…”
Section: Infantsmentioning
confidence: 99%
“…The adjusted multivariate analysis showed that a longer LOS, necessity of nutrition intervention, and clinical complications were significantly associated with NR. Hospital LOS was higher in patients with higher NR scores in five studies 31,39,49,50,68 . There was a higher chance of longer hospitalization reported in the studies that used the STRONGkids, varying between 1.66 49 and 8.02 50 .…”
Section: Resultsmentioning
confidence: 85%